PENGARUH PENERAPAN GREEN ACCOUNTING DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP PROFITABILITAS - Angela, Nova; Espa, Vitryan; Yantiana, Nella (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2024)
Environmental damage caused by companies is an important issue to discuss. Currently, many companies only focus on the production process and increasing profits without thinking about the impacts. Therefore, environmental accounting was born which became part of the problem in order to overcome this problem. This research aims to examine the impact of implementing Green Accounting and Corporate Social Responsibility on Profitability in Oil and Gas Sub-Sector Mining Companies listed on the IDX in 2020-2023. This research uses a quantitative type using a purposive sampling information collection method. Bibliography techniques are used with secondary information obtained through annual reports and company sustainability reports. This method is used via SPSS software via a type of multiple linear regression analysis. The results of the research showed that Green Accounting had a positive impact on Profitability, while Corporate Social Responsibility had no impact.